Crowds and the timing of goals and referee decisions - Magee, C.; Wolaver, A. (Journal of Sports Economics, 2023)
This paper investigates how crowds affect the timing of events during football matches. In theory, the presence of fans influences the urgency of the players on the field, and the magnitude of this effect grows during the match. Thus, crowds should lead to a faster increase during the match in goals scored, yellow cards, red cards, and penalty kicks. We test the hypothesis using a data set including pandemic ghost games and we find strong support for the hypothesis as it relates to goals, yellow cards, and penalty kicks but not as it relates to red cards.